Zróżnicowanie reżimu odpływu rzek w północno-zachodniej Polsce - Wrzesiński, Dariusz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
This paper seeks to identify features of the flow regime of rivers in north–western Poland in terms of runoff, structure, as well as temporal and spatial variability. The analysis was performed on the basis of hydrometric data of the Institute of Meteorology and Water Management from the years 1951-2010 coming from 46 gauging stations located on 33 rivers. The research embraced coastal rivers and lakeland tributaries of the Oder, Noteć and Vistula. In hydrological terms, this area is characterised by wide differences in flow conditions, as indicated by both, very great and very low water abundance. As a result, those rivers have different regime features, and on the basis of regularities in their flow variability they can be classified into 3 varieties of the nival hydrological regime. The rivers in this area display exceptional differences in total runoff, from the lowest values in the entire country (under 100 mm, the upper Noteć basin), to very high, the highest in the lowland part of Poland (over 300, and in the case of the Radunia even over 400 mm). They also show wide differences in their groundwater flow and its contribution to total runoff. For many coastal rivers this figure exceeds 80%, the highest in the country. Another of their characteristics is the lowest variability of discharges, especially annual ones. Also notable are the distinctly greater water abundance, higher groundwater flow and its share in total runoff, as well as lower variability of yearly discharges of streams in the eastern part of the coastal region than in its western area.
Keywords: river runoff; hydrological regime; Poland